Analysis of the impact of Type I cement with feldspar addition on the heat of hydration and compressive strength - CARRION RABANAL, KATIA NATALY; Medina Cabanillas, Edwar Sleyter (LACCEI, 2025)
This study show, the influence of the use of a Portland cement type I, modified with feldspar on the heat of hydration and compressive strength was investigated, to analyze the effect on the heat of hydration, a concrete with a fluid consistency design and compressive strength of f'c = 250 kg / cm2 was prepared, based on Portland cement type I modified with 5%, 10% and 15% with respect to the weight of the cement, to make the analysis the concrete exudation test was performed, for this 12 cylindrical specimens were prepared. The results showed that the greater the addition of feldspar, the less exudation and the heat of hydration tends to increase. However, in the C15F mixture it is observed that there is less exudation and the heat of hydration decreases, which can minimize thermal cracking in massive concretes. Regarding the compressive strength of the mortars, it was shown that with the C10F mixture a resistance 10% higher than the others was obtained.